Are We Asking the Right Questions? A Response to the Academic Reforms Research the NCAA - Fields, Sarah K. (Journal of Intercollegiate Sport, 2012)
The purpose of this paper is to respond to the papers presented by Petr and McArdle (2012) and Paskus (2012). The author questions whether the appropriate issues are being addressed in broader academic reform efforts, and whether the data collected help the prime beneficiaries of intercollegiate athletics: the athletes. Questions pertaining to gender, race, and first-generation status are also posed.